Corpus-Based Analysis of the Meaning & Translation of The Arabic Word Ghurfah (غرفة) in Islamic Discourse - Al-Maslami, Arwa Mahmoud Fara'a Mohamed et al. (University of Science and Technology, Sana'a, Faculty of Humanities and Social Sciences, Translation Program, 2023)
This research aims to investigate the meaning of the polysemous and homonymous word 'Ghurfah' (غرفة) in the Arabic language. In addition, it examines the contextual application of the word within the Arabic corpus and sheds light on its various English translations in the Holy Qur'an. Following a descriptive and content-based analytical methodology, the study revealed that the word 'Ghurfah' is repeated 5 times in the Holy Qur'an, conveying two distinct meanings: the act of scooping a handful of water, and an elevated place or chamber in Paradise. In the wider Arabic corpus, the findings indicate that the most common meaning of 'Ghurfah' is a physical place or room, followed by virtual or metaphorical usage, a place in Paradise, and lastly, the measure of water taken in one's hand. Furthermore, lexicographical analysis shows that the predominant modern usage signifies a space enclosed by four walls—a room, as defined by the Longman Dictionary (a part of the inside of a building that has its own walls, floor, and ceiling). Finally, the researchers clarified the semantic nuances by analyzing the Qur'anic interpretations and translations of Abdullah Yusuf Ali and Mohammad Habib Shakir, who accurately reflected these dual meanings with subtle contextual differences.